High-sensitivity neutron diffraction of membranes: Location of the Schiff base end of the chromophore of bacteriorhodopsin - Heyn, M. P. (1988)
Three important events in the functional cycle of bacteriorhodopsin occur at the chromophore: the primary absorption of light, the isomerization from the alltrans to the 13-cis form, and the deprotonation and reprotonation of its Schiff base. The protonated Schiff base linkage of the chromophore with lysine-216 plays an essential role in the color regulation of the pigment and is most likely directly involved in the charge translocation of this light-driven proton pump. Although much is known about the structure of the protein, the position of this key functional group has not yet been determined. We have synthesized a retinal in which the five protons closest to the Schiff base are replaced by deuterons. The labeled retinal was spontaneously incorporated into bacteriorhodopsin by using a mutant of Halobacterium halobium that is deficient in the synthesis of retinal. The position of the labeled Schiff base end of the chromophore was determined in the two-dimensional projected density of dark-adapted bacteriorhodopsin by neutron diffraction. The result fits very well with our previous work using retinals that were selectively deuterated in the middle of the polyene chain or in the cyclohexene ring. A coherent structure emerges with the three labeled positions on one line, separated by distances that are in good agreement with the tilt angle of the polyene chain (about 20°). The chromophore is located in the interior of the protein with the nitrogen of the Schiff base between helices 2 and 6 and with its ring in the vicinity of helix 4. Our results show that it is possible to locate a small group containing as few as five deuterons in a membrane protein of molecular weight 27,000.